Intra- and intermolecular interactions of human galectin-3: assessment by full-assignment-based NMR - Ippel, Hans; Miller, Michelle C.; Vértesy, Sabine; Zheng, Yi; Cañada, F. Javier; Suylen, Dennis; Umemoto, Kimiko; Romanò, Cecilia; Hackeng, Tilman; Tai, Guihua; Leffler, Hakon; Kopitz, Jürgen; et al. (Glycobiology, 2016)
Abstract. Galectin-3 is an adhesion/growth-regulatory protein with a modular design comprising an N-terminal tail (NT, residues 1-111) and the conserved carboh